POLLEN DISPERSAL PATTERNS EBONI LASITAE PROVENANCE BASED ON SIMPLE SEQUENCE REPEATS (SSR) - Muhammad Restu; Gusmiaty .; Siti Halimah Larekeng (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2016)
Parentage analysis has been used to evaluate pollen dispersal in ebony (Diosphyros celebica Bakh.). The objectives of this research were to evaluate (i) the dispersal of pollen, and (ii) the distance of pollen travel in ebony Lasitae provenances. The finding of this activities should be beneficial to support breeding of this ebony tree. There were 14 progeny arrays were harvested from 3 female parents. There were 32 ebony trees surrounding the female parents were analyses as the potential male parents for the progenies. Ebony tress were mapped according to their GPS position. All samples were genotyped using four SSR marker loci. Parentage analysis was done using CERVUS version 2.0 software. Results of the analysis indicated the evaluated markers were effective for assigning candidate male parents to all evaluated seedlings. There is no specific direction of donated pollen movement from assigned donor parents to the female ones. The donated pollens could come from assigned male parents in any directions relative to the female parent positions. Pollen dispersal pattern of ebony female parent occured in outcrossing pollination among its different donated trees. Based on the progenies analysis, ebony female parent is a dominantly outcrossing pollination species. Distances of pollen travel reach to 18 until 269 meter.Key words: Ebony, ssr marker, pollen dispersal.